Scope (Objects and Targets) of Educational Supervision - Abdurrahman; Eva Zakiyatul Fakhiroh; Hurriyatul Ifadhah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Education is a process, as well as an effort to humanize humans so that they are in accordance with the goals to be achieved. Supervision as a controller of education components, especially teachers as implementers. The essence of educational supervision is the process of mentoring from superiors to teachers and other school stake holders who deal directly during the student learning process, to improve teaching and learning conditions so that students can learn effectively which is marked by increasing learning achievement. Theoretically, the object of supervision has two aspects, the human aspect and the activity aspect. Meanwhile, in terms of the object being supervised, there are three kinds of supervision, namely: (1) academic supervision; (2)administrative supervision; and (3) institutional supervision. Some things that are supervised by school supervisors include: curriculum, student affairs, staffing, facilities and infrastructure, finance, and public relations.